The role of meteorological variables of blossoming and ripening within the tendency of qualitative indexes of sour cherry - Lakatos, L.; Szabó, T.; Sun, Z.; Soltész, M.; Szabó, Z.; Dussi, M. C.; Nyéki, J. (International Journal of Horticultural Science, 2010)
We analyzed the relationship to sour cherry quality parameters of average temperature, maximum temperature, minimum temperature, night and day-time temperature, precipitation and climatic water balance variables. Three cultivars of sour cherry were included in the selection: “Debreceni bôtermô”, “Kántorjánosi”, and “Újfehértói fürtös”.We conducted regression analyzes on the three varieties, but present only those that proved to be the best fit.We couldn’t find any significant differences in the weather tolerance of the varieties. The data base of sour cherry quality parameters covers the 1998 to 2008 intervals. The researched parameters were the following: dry matter content (%), sugar content (%), C-vitamin (mg), total acid content (%). Maximum temperature, the difference of night and day-time temperature and minimum temperature all have a significant correlation with the investigated quality parameters of sour cherry. Minimum temperature shows a quadratic relationship with sugar content, while night and day-time temperature differences show the same with dry matter content. The other weather parameters had a linear correlation with the quality parameters of sour cherry. The research results show that an increasing amount of precipitation causes decreasing tendency in total acid content of sour cherry, so that increasing temperature has a positive influence on total acid content. Big differences in night and day-time temperature also has positive effects on the dry matter and sugar content of sour cherry while the amount of precipitation has a negative effect. High minimum temperatures cause decreasing sugar content respiratory energy losses are significant if dawn temperatures do not drop considerably.A more favourable climatic water balance has a positive effect on vitamin C content in cases of a large negative water balance, vitamin C content is generally low.